2017
DOI: 10.1007/s10006-017-0657-7
|View full text |Cite
|
Sign up to set email alerts
|

Can gray values derived from CT and cone beam CT estimate new bone formation? An in vivo study

Abstract: According to the results, both HU/CT and GV/CBCT can be considered as fairly good predictors for assessment of the amount of NBF following bone reconstruction surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
2
1
1
Order By: Relevance
“…The mean gray values obtained by a CBCT scan and HUs in a CT scan show a strong correlation [33]. Contrary to results of the present investigation, the study by Batsami et al showed that the gray values from a CBCT scan of rabbits can be used to assess bone quality and the amount of new bone formation before implant placement [34]. Gonzáles-Garcia and Monje found a significant correlation between the gray values of a CBCT scan and the bone density in biopsies of the upper jaw.…”
Section: Measurements Of Bone Densitycontrasting
confidence: 75%
“…The mean gray values obtained by a CBCT scan and HUs in a CT scan show a strong correlation [33]. Contrary to results of the present investigation, the study by Batsami et al showed that the gray values from a CBCT scan of rabbits can be used to assess bone quality and the amount of new bone formation before implant placement [34]. Gonzáles-Garcia and Monje found a significant correlation between the gray values of a CBCT scan and the bone density in biopsies of the upper jaw.…”
Section: Measurements Of Bone Densitycontrasting
confidence: 75%
“…The validity of CBCT bone measurements as an index of bone quality was questioned (Harris et al, ), but its reliability to objectively assess the density of bone has not been properly studied in human clinics (Gonzalez‐Garcia & Monje, ). A recent published in vivo study reported Hounsfield unit derived from computed tomography (HU/CT) and gray value derived from cone beam computed tomography (GV/CBCT) may be considered as fairly good predictors for assessment of the amount of new bone formation following bone reconstruction surgeries (Bastami et al, ). The finding was corroborated by a study that was evaluating the variability of intensity values in CBCT imaging compared with MSCT HU units in order to assess the reliability of density assessments in bone biopsies of the maxillary bones (Gonzalez‐Garcia & Monje, ).…”
Section: Discussionmentioning
confidence: 99%
“…Existe controversia respecto de la evaluación de hueso por medio de la TCHC, que utiliza una escala de grises en comparación con las unidades Hounsfield de la TCM. La escala de grises no permite una conversión directa a unidades Hounsfield, pero sí establecer una relación lineal entre ambas para la evaluación de las diferentes densidades de los tejidos en una TCHC, así como para mediciones que evalúan la formación de hueso ( [61][62][63] ).…”
Section: Tchc De La Estructura Craneofacial En Neurología Y Neurocirugíaunclassified